2018
DOI: 10.1038/s41418-017-0010-6
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 and Bcl-xL sequestration of Bak confers differential resistance to BH3-only proteins

Abstract: The prosurvival Bcl-2 family proteins Mcl-1 and Bcl-x inhibit apoptosis by sequestering BH3-only proteins such as Bid and Bim (MODE 1) or the effector proteins Bak and Bax (MODE 2). To better understand the contributions of MODE 1 and MODE 2 in blocking cell death, and thus how to bypass resistance to cell death, we examined prescribed mixtures of Bcl-2 family proteins. In a Bim and Bak mixture, Bcl-x and Mcl-1 each sequestered not only Bim but also Bak as it became activated by Bim. In contrast, in a Bid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 60 publications
3
39
1
Order By: Relevance
“…In the present study, we report that the AMPK-Mfn1 pathway is closely regulated by resveratrol. 74,75 This finding provides an easy and effective approach to activate protective the AMPK-Mfn1 pathway in the setting of cerebral IR injury. 76…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, we report that the AMPK-Mfn1 pathway is closely regulated by resveratrol. 74,75 This finding provides an easy and effective approach to activate protective the AMPK-Mfn1 pathway in the setting of cerebral IR injury. 76…”
Section: Discussionmentioning
confidence: 88%
“…The prosurvival BCL-2 proteins, especially MCL-1 and BCL-X L , can sequester activated BAK, an inhibition process referred to as Mode 2 [27][28][29][60][61][62] (see Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…The unfolded activated BAK and BAX monomers can then dimerize via reciprocal BH3:groove interactions to form "symmetric homodimers" 12,13,[16][17][18][19][20][21][22] that cluster on the MOM to release apoptogenic factors from the mitochondrial intermembrane space [23][24][25] . Alternatively, the activated BAK and BAX monomers may bind to prosurvival members to form heterodimers that do not participate in pore formation [26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that Bcl‐2 sequesters BH3 domain‐only molecules including Bad, Bim, and NOXA in stable mitochondrial complexes, inhibiting the activation of Bak and Bax . Furthermore, Hockings et al have reported that Mcl‐1 preferentially sequesters Bak in resistance to anticancer treatments, including BH3 mimetics. Our data showed that ascleposide significantly downregulated Bcl‐2 and Mcl‐1, while upregulated Bak protein expression, suggesting the contribution of the Bcl‐2 family members to mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%